Drug abuse and drug addiction among students of University of Rajshahi - Faiqua Tahjiba (Bangladesh Journal of Bioethics, 2020)
Objectives: The aim of this study was to investigate the actual condition of the students of University of Rajshahi (RU) regarding drug abuse and addiction. Using case study method the research was conducted with four objectives: (a) to find out how respondents began drug abuse; (b) to discover the causes of their drug addiction; (c) to understand the process of their drug abuse; and (d) to find out the economic, social and health effects of drug abuse. Methods: Case study method was used in this research. Through snowball sampling 18 drug- addicted students of RU were selected as respondents. In-depth interview with a schedule was used to collect data from the respondents in January 2019. Results: Findings of the study show that the causes of drug addiction included curiosity, frustration, friends’ request, neglect from family and friends etc. The drugs which they usually abused were Yaba, Phensydyle, Ganja (Weed), Chuani etc. Their average monthly expenditure for collecting drugs was in between Taka 8,000-10,000. They collected those drugs from rickshaw pullers at different points within the campus and from Mizaner Mor, Budhpara slum and other places outside the campus. The respondents opined that drugs were available if sufficient money could be spent. The respondents had senior and junior fellow students and local boys as companions while taking drugs. Most of them faced physical problems after taking drugs, and some of them tried to get rid of this curse of drug addiction. Conclusion: The findings of this research show that the rate of drug addiction among the students of RU was quite alarming. Therefore, all stakeholders including the students, guardians, teachers, university authority, the law makers and law enforcing agencies, researchers, civil society, NGO’s and the state must come forward together to combat this formidable foe.